A proposal of communication protocols in ubiquitous computation environment in the residential automation - Pérez, Celso Roberto (2008)
An ubiquitous computation environment has as presupposed that the computation is in all equipment and devices, and these are interacting between itself and with the people. The connection between objects and human beings is instantaneous, when these enter in the ubiquitous environment. A communication protocol to make the linking between many devices, of many manufacturers, in this environment, will be the key so that this connectivity happens. In the industrial automation, the protocol RS 485, is very used. Although some similarities in the intentions, the residential automation has different concepts from the industrial. The protocol I2C, of the wire technology, developed by Philips, appears as option for the residential automation. Protocols of wireless technology, as bluetooth and zigbee, because of its characteristic of covering, are presented as complement for this automation. This article aims to present a vision about the necessary characteristics of the communication protocols for a ubiquitous computation environment in the residential automation. In it will be described the studies, development and implantation of devices of residential automation that occurs in the QualiHouse Residential Automation, incubated company in the Trilha, pre-incubator of the Faculdade Integrada do Recife - FIR.